Karakteristik Verba pada Laki-Laki dan Perempuan dalam Kolom Komentar YouTube Narasi Newsroom - Melinda, Dika; Putra, Dona Aji Karunia (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research aims to describe the forms of verbs for men and women grammatically and social side; describe the semantic types of verbs for men and women grammatically and social side in the comments column of Narasi Newsroom’s Youtube. The research method used in this research is a descriptive method with a qualitative approach. The data in this study are the use of verbs used by men and women in the YouTube Narration Newsroom comments column. Data collection techniques consist of documentation techniques, comprehending and note-taking techniques. Data were analyzed using verb theory and language and gender theory. The result showed that there are 205 forms of verbs used by men, 238 forms of verbs used by women, 114 semantic types of verbs used by men, and 135 semantic types of verbs used by women. Characteristics of verb forms based on social side between men and women languages could be seen in the terms of diction and morphology in the form of affixation. Based on the aspect meaning, women use symbolic language while men use direct language at problem points. Women interact by increasing solidarity while men by maintaining power and status. The topic of conversation for women focuses on affective functions while men on competence.